Mediating Roles of Impulsivity and Risk Taking in the Links of the Dark Triad with Flirting and Dating via Social Media - Zeynep Işıl Demircioğlu; Aslı Göncü Köse (Psikoloji Çalışmaları)
With the acceleration of communication and access to information, individuals have begun to date via social networking sites. Although online dating has spread among university students recently, studies on this topic are very limited. The present study aimed to investigate the effects of the Dark Triad personality traits (i.e., Machiavellianism, psychopathy, and narcissism) on using Social Networking Sites (SNS) to find partners and face-to-face meeting/dating after flirting via the internet (i.e., face-to-face dating with a partner met via SNS). Furthermore, it was also aimed to identify the mediating roles of risk-taking and impulsivity in the relationships mentioned above. Data were collected from 358 University students (223 females and 135 males) who volunteered to complete the survey packages. The data was analyzed using Structural Equation Modeling (SEM). The age of the participants ranged between 18 and 49 (M = 22.67, SD = 2.83). The results revealed that narcissism was linked to using SNS to find partners, and impulsivity fully mediated the relationships of Machiavellianism with using SNS to find partners. In addition, the links of psychopathy with using SNS to find partners were partially mediated by impulsivity, with risk-taking fully mediating the effects of psychopathy and narcissism on face-to-face dating with a partner met via SNS. The present research revealed that impulsivity and risk-taking were the common attitudes underlying the links of psychopathy and narcissism with dating someone met via SNS. For individuals who score high on Machiavellianism, a low level of impulsivity is a protective factor; whereas a high level of impulsivity is a triggering factor that leads those with high psychopathy scores to search for partners via SNS. Contrary to expectations, narcissism was not directly associated with face-to-face dating a partner who was met via SNS. This finding may be related to the unidimensional measurement of narcissism, since grandiose narcissism is more likely to be positively associated with this risky and confident behavior, whereas vulnerable narcissism is less likely to have such an association.